TEORI BELAJAR KONSTRUKTIVISME DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN - Desi Wenda; Ramina Wasiangge; Sance Syakema; Tius Kogoya; Meilany Kemesrar (CV. Adiba Aisha Amira, 2026)
This study is motivated by the importance of learning that not only focuses on content delivery but also emphasizes students’ active involvement in constructing understanding and living out faith values. The constructivist approach is considered capable of creating meaningful, contextual learning while shaping character and spirituality. This study aims to examine constructivist learning theory and its relevance in Christian Religious Education. The method used is a library research approach with descriptive qualitative analysis of various scientific sources. The results show that constructivism aligns with the goals of CRE as it emphasizes deep understanding and lived faith experiences. Its implementation through discussions, reflection, case studies, and role-playing encourages active student participation. Existing challenges can be addressed through proper planning and improving teacher competence, making learning more effective and meaningful.